Contribution to Tumor Angiogenesis From Innate Immune Cells Within the Tumor Microenvironment: Implications for Immunotherapy - Albini, Adriana; Bruno, Antonino; Noonan, Douglas M.; Mortara, Lorenzo (Frontiers in Immunology, 2018)
The critical role of angiogenesis in promoting tumor growth and metastasis is strongly established. However, tumors show considerable variation in angiogenic characteristics and in their sensitivity to anti-angiogenic therapy. Tumor angiogenesis involves not only cancer cells, also a variety of tumor-associated leukocytes (TALs) and stromal cells. TALs produce chemokines, cytokines, proteases, structural proteins and microvescicles. Vascular endothelial growth factor (VEGF) and inflammatory chemokines are not only major pro-angiogenic factors but are also immune modulators, which increase angiogenesis and lead to immune suppression. In our review, we discuss the regulation of angiogenesis by innate immune cells in the tumor microenvironment, specific features and roles of major players: macrophages, neutrophils, myeloid-derived suppressor and dendritic cells, mast cells, T cells, innate lymphoid cells and natural killer cells. Anti-VEGF or anti-inflammatory drugs could balance an immune suppressive microenvironment to an immune permissive one. Anti-VEGF as well as anti-inflammatory drugs could therefore represent partners for combinations with immune checkpoint inhibitors, enhancing the effects of immune therapy.